1993
DOI: 10.1128/jb.175.8.2197-2204.1993
|View full text |Cite
|
Sign up to set email alerts
|

Genetic construction and functional analysis of hybrid polyketide synthases containing heterologous acyl carrier proteins

Abstract: The gene that encodes the acyl carrier protein (ACP) of the actinorhodin polyketide synthase (PKS) of Streptomyces coelicolor A3(2) was replaced with homologs from the granaticin, oxytetracycline, tetracenomycin, and putative frenolicin polyketide synthase gene clusters. All of the replacements led to expression of functional synthases, and the recombinants synthesized aromatic polyketides similar in chromatographic properties to actinorhodin or to shunt products produced by mutants defective in the actinorhod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 26 publications
(23 reference statements)
5
44
0
Order By: Relevance
“…The observation that ACP is needed in substantially more than stoichiometric amounts compared with the KS/CLF for maximal activity is consistent with earlier genetic studies where alterations in expression levels of the ACP gene resulted in significant differences in polyketide production in vivo (28). It suggests that the ACP interacts only loosely with the PKS core comprised of the KS and CLF.…”
Section: Discussionsupporting
confidence: 89%
“…The observation that ACP is needed in substantially more than stoichiometric amounts compared with the KS/CLF for maximal activity is consistent with earlier genetic studies where alterations in expression levels of the ACP gene resulted in significant differences in polyketide production in vivo (28). It suggests that the ACP interacts only loosely with the PKS core comprised of the KS and CLF.…”
Section: Discussionsupporting
confidence: 89%
“…Quantitative differences in hybrid PKS products were attributed to the differences in the upstream ribosomal binding sites, which probably affect the level of expression or efficiency of translation. The strong quantitative variation in total aromatic polyketide production was found to be either because of limiting ACP concentration or some level of translational coupling (41). Many in vitro and in vivo studies have confirmed that by increasing ACP concentration the level of antibiotic production can be increased.…”
Section: Role Of Tandemly Repeated Acyl Carrier Proteinsmentioning
confidence: 98%
“…Only in the cases of the tetracenomycin (40) and actinorhodin (5,19,34,55) PKSs, however, have biochemical characterizations also been carried out. Thus, most of the information on type II PKSs is derived from the strong conservation of gene structure among the PKS genes (23,25) and cross-functionality of the components (5,26,34,41). We describe here the structure of a gene region from Streptomyces sp.…”
mentioning
confidence: 99%